The Relationship between the Fear of Missing Out (FoMO) and Social Media Use in Articulating Islamic Identity among Muslim Millennials - Ginting, Elisa Br; Suwarjo, Suwarjo; Lumbanbatu, Johannes Sohirimon; Sihotang, Din Oloan (Universitas Muhammadiyah Yogyakarta, 2023)
Current technological developments have both positive and negative impacts. One of the negative impacts of excessive social media is that it can lead to addiction, cyberbullying, and fear of missing out (FOMO). It can even erode one's identity, as widely circulated videos on social media influence it. This research aims to analyze the relationship between FOMO, problematic use of social media, and expressions of Islamic identity. This research used the FoMO scale, social media disorder scale, and Instagram Islamic identity scale as measuring tools. A quantitative approach was employed, using multiple analyses, which revealed that FOMO and problematic use of social media simultaneously contribute to expressing Islamic identity. The subjects of this research were 177 Indonesian millennial Muslims who actively participated in the Instagram migration movement. Problematic use of social media and expression of Islamic identity effectively contributed 40.6% (36.7% from social media use and 3.9% from FOMO). Additionally, questionable social media use had a significant correlation with the articulation of Islamic identity, while FoMO itself did not correlate with it. These results can serve as a basis for future research on the expression of religious identity on social media and the development of interventions to address excessive social media use.